Cortical Blindness, Transient and Otherwise, Associated with Detachable Coil Embolization of Intracranial Aneurysms - Niimi, Y.; Kupersmith, M.J.; Ahmad, S.; Song, J.; Berenstein, A. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Cortical visual loss is a rare complication of cerebral angiography without a definitive pathophysiology. Given the rapid increase in endovascular procedures used to treat cerebral aneurysms, we explored the prevalence of this complication and whether we could add to the understanding of this disorder.Materials and METHODS: We performed a retrospective review of all procedures performed with the same contrast agent and detachable coils for treatment of posterior circulation aneurysms by 1 endovascular surgery service from 1996 to 2006. All patients were evaluated before and after each procedure by a team that included a neuro-ophthalmologist.RESULTS: Of 137 intra-arterial treatment procedures performed for posterior circulation aneurysms, we identified 4 patients with cerebral vision loss complications. During the same time period, >500 aneurysms of the anterior cerebral circulation were treated without this complication. The visual field loss was unilateral in 2 and bilateral in 2 patients. Recovery was complete in 3 and almost normal in the fourth patient. The amount of contrast used and the duration of the procedure were similar among all patients. The 4 patients had no identified specific risk factors for developing procedure-associated occipital dysfunction, all 4 had undergone prior angiography, and 1 patient had undergone repeat coiling, without complication.CONCLUSION: The 2.9% prevalence of cerebral visual loss with endovascular coil treatment of posterior circulation aneurysms is higher than that for angiography alone. Our patients recovered well with corticosteroid and intravenous hydration treatment. Recognizing the self-limiting nature of this problem might prevent an unneeded intervention.